2005
DOI: 10.1002/bit.20500
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acetate and propionate uptake by polyphosphate accumulating organisms and glycogen accumulating organisms

Abstract: Enhanced biological phosphorus removal (EBPR) performance is directly affected by the competition between polyphosphate accumulating organisms (PAOs) and glycogen accumulating organisms (GAOs). This study investigates the effects of carbon source on PAO and GAO metabolism. Enriched PAO and GAO cultures were tested with the two most commonly found volatile fatty acids (VFAs) in wastewater systems, acetate and propionate. Four sequencing batch reactors (SBRs) were operated under similar conditions and influent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
141
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 245 publications
(160 citation statements)
references
References 24 publications
16
141
2
1
Order By: Relevance
“…Recent studies have suggested that a propionate feed source is more beneficial for reliable EBPR performance than acetate (Chen et al, 2004;Oehmen et al, 2005aOehmen et al, , 2006Pijuan et al, 2004;Thomas et al, 2003), likely due to a reduced level of GAO activity. The metabolic activity of PAOs and GAOs fed with different carbon sources is compared in Further investigation is required to assess the proliferation of these Alphaproteobacteria GAOs in EBPR plants as well as their ability to compete with PAOs in these systems.…”
Section: Impact On the Competition Between Paos And Gaosmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have suggested that a propionate feed source is more beneficial for reliable EBPR performance than acetate (Chen et al, 2004;Oehmen et al, 2005aOehmen et al, , 2006Pijuan et al, 2004;Thomas et al, 2003), likely due to a reduced level of GAO activity. The metabolic activity of PAOs and GAOs fed with different carbon sources is compared in Further investigation is required to assess the proliferation of these Alphaproteobacteria GAOs in EBPR plants as well as their ability to compete with PAOs in these systems.…”
Section: Impact On the Competition Between Paos And Gaosmentioning
confidence: 99%
“…Accumulibacter appears to be a dominant PAO in the presence of both acetate and propionate as carbon sources, and has been shown to have the capacity to switch between acetate and propionate uptake without the need for acclimation (Oehmen et al, 2005a;Pijuan et al, 2004). It is possible, however, that GAOs have a more specific preference for acetate or propionate.…”
Section: Impact On the Competition Between Paos And Gaosmentioning
confidence: 99%
See 2 more Smart Citations
“…GAOs also take up and store organic carbon under anaerobic conditions but do not cycle P i (anaerobic release and aerobic uptake), and their selective enrichment over PAOs via competition for sparingly available VFAs in EBPR plants leads to excessive P i in plant effluents (Liu et al, 1996;Mino et al, 1995). Lab-scale (Bond et al, 1999;Oehmen et al, 2005) and full-scale (Kong et al, , 2006Saunders et al, 2003) EBPR studies showed this PAO-GAO competition for VFAs. Pure cultures that display the PAO or GAO phenotype as described above have not yet been acquired Seviour et al, 2003).…”
Section: Introductionmentioning
confidence: 99%